Digital Financial Inclusion and Poverty Reduction in the SDGs Era: A Study in Indonesia - Anis Rudianto Rudianto; Muhammad ghufron; Nurul Mustapa (IJED: International Journal of Economy Development Research, 2026)
This study examines the role of digital financial inclusion in reducing poverty in Indonesia within the framework of the Sustainable Development Goals (SDGs). Digital financial inclusion is increasingly viewed as a strategic instrument for expanding access to formal financial services, particularly for low-income households, micro-enterprises, rural communities, women, and previously unbanked populations. Indonesia provides an important case because the country has experienced rapid digital financial transformation through mobile banking, e-wallets, QRIS, branchless banking, fintech lending, and digital government-to-person payments. At the same time, poverty reduction remains a central development agenda. BPS reported that Indonesia’s poverty rate declined to 8.47 percent in March 2025, equivalent to 23.85 million people, and further declined to 8.25 percent in September 2025, equivalent to 23.36 million people. Using a qualitative-descriptive approach supported by secondary data from BPS, OJK, Bank Indonesia, World Bank, and relevant academic literature, this study analyzes the mechanisms through which digital financial inclusion contributes to poverty reduction. The findings indicate that digital financial inclusion supports poverty reduction through four main pathways: expanding access to savings and payments, improving access to productive credit, strengthening micro and small enterprises, and increasing the efficiency of social assistance distribution. However, the study also finds that digital financial inclusion does not automatically reduce poverty unless supported by digital literacy, consumer protection, equitable infrastructure, affordable internet access, and inclusive regulatory frameworks. OJK’s 2024 national survey showed Indonesia’s financial literacy index at 65.43 percent and financial inclusion index at 75.02 percent, indicating progress but also a remaining gap between access and effective use.mThe study concludes that digital financial inclusion can become a powerful SDGs-oriented poverty reduction instrument in Indonesia when it is integrated with inclusive economic policy, MSME empowerment,  social protection reform, and digital capability development. The main contribution of this article is to position digital financial inclusion not merely as a technological innovation, but as a development strategy that must be socially embedded, institutionally regulated, and directed toward distributive justice.